Carcinogenic effects of n-methyl-n-nitrosourea administered via oral and intraperitoneal routes in female sprague dawley rats - Mohd Kassim, Muhammad Hakimi (2014)
N-methyl-N-nitrosourea (MNU) is able to induce multiple tumours via different routes of administration. The development of tumours is well associated with failure of apoptosis process. In cancer studies, real time quantitative reverse transcription polymerase chain reaction (qRT-PCR) is widely used to measure changes of the messenger ribonucleic acid (mRNA) level of targeted genes. To date, there is no comparative study of the carcinogenic effects of MNU between administration via oral and intraperitoneal (IP) routes. Besides comparing the apoptotic genes normalization using single and multiple housekeeping (HK) genes, changes of the expression of the targeted apoptotic gene during the carcinogenesis in whole blood and spleen between all groups and their correlation to the lesion scoring in the selected organs remained undetermined. The main objective of this study was to compare the carcinogenic effects of MNU post administration via oral and IP routes through blood profiles, urinalysis, gross and histopathological examination. Comparison of apoptotic genes normalization using single and multiple HK genes, the levels of Bcl-2 to Bax fold expression ratios in whole blood and spleen and their correlations to the lymphoma lesion scores served as the second, third and fourth objectives in this study. A total of 27 female Sprague Dawley (SD) rats was separated equally into three groups which were control (group A), MNU-treated orally (group B) and MNU-treated intraperitoneally (group C). Rats in MNU-treated groups received 60 mg/kg of body weight MNU twice a week for two consecutive weeks which equal to a total dose of 240 mg/kg of body weight. Rats in control group received normal saline following the same procedure. All rats were humanely sacrificed after 6 months of animal study. In addition to IP route, oral administration of MNU successfully induced leukaemia in all rats and emerged as a new promising route to induce this cancer. Administration of MNU regardless of routes contributed to the elevation of Bcl-2 to Bax fold expression ratios leading to overproduction of neoplastic cells observed in the blood smear with a prominent occurrence of lymphocytosis in rats administering MNU intraperitoneally. Introduction of MNU into the intraperitoneum cavity led to rapid absorption and higher bioavailability of this carcinogen which in turn, significantly increased serum urea, AST, LDH and reduced TP concentrations respectively. Regardless of administration routes, significant reduction of creatinine clearance (CrCl) and elevation of urine protein to creatinine (UPC) ratios post administration of MNU reflecting the renal insufficiency of rats even though the renal lymphoma severity averagely mild. The incidences of splenomegaly with higher prevalence, hepatomegaly and stomach mass were related to the enteral process conferred by oral route of administration. Intraperitoneal route of MNU administration inferred as a reliable route to promote the development of mammary gland tumours of multiple types as there was no incidence of this type of tumour in rats administered the carcinogen orally. Administration of MNU regardless of routes contributed to no significant differences in terms of the incidence of splenomegaly, percentage of splenic lymphoma and lesion scores and these findings were further confirmed by the real time qRT-PCR as a more sensitive method showing nearly similar splenic fold expression ratios of Bcl-2 to Bax. Lungs emerged as a non-haematopoietic target organ for leukaemia dissemination due to increased weight of lungs, high incidence of pulmonary lymphoma and severity of lymphoma lesion were insignificantly difference in rats administered MNU via both routes. The leukaemia induced post administration of MNU regardless of routes played a prominent role as a systemic disease as it was able to metastasise to all selected organs with higher affinity to lungs and heart observed in rats having intraperitoneal administration as compared to oral administration of the carcinogen. Administration of MNU regardless of routes could impart nearly similar lymphoma lesion severity reflected by lesion scores. The application of both glyceraldehydes-3-phosphate dehydrogenase (GAPDH) and β-actin for normalisation purpose produced more reliable and precise expression data as outlier or error associated with any individual set of data was averaged out leading to reduced data dispersion. At the molecular level, Bcl-2 to Bax fold expression ratios in whole blood and spleen post administration of MNU regardless to routes were significantly increased at nearly similar expression patterns promoting cell proliferation of neoplastic cells showed in the blood smears and also massive proliferation of neoplastic cells in spleen. It was further inferred that measuring Bcl-2 to Bax fold expression ratios in whole blood was suffice to detect the presence and severity of lymphoma in the selected organs. Conclusively, the application of real time qRT-PCR using Bcl-2 to Bax fold expression ratio in whole blood as the panel to detect and decipher the severity of lymphoma lesion was reliable and more accurate rather than the invasive method.